IMPLEMENTASI PROGRAM KELUARGA HARAPAN TERHADAP PENINGKATAN KESEJAHTERAAN RUMAH TANGGA SANGAT MISKIN DI KABUPATEN SUMBAWA - Karmeli, Elly; Sapitri, Weli Alia (Pusat Riset dan Publikasi, 2024)
This study aims to analyze the effect of implementation the Family Hope Program (PKH) on improving the welfare of very poor households in Sumbawa District. The type of this study was associative study. The type of data used was quantitative data obtained directly from primary sources, namely the PKH recipient community in Sumbawa District who were the respondents. The number of samples that will be used as respondents for this study was 68 people who were determined using probability sampling techniques with a simple random sampling method. The primary data used in this study was collected using a questionnaire as an instrument which was measured using a Likert Scale with four alternative answers provided. All of data was processed using the SPSS program to be analyzed and interpreted using simple linear regression analysis techniques, partial hypothesis testing (t test), and coefficient of determination test (R2). The results of this study showed that the implementation of Family Hope Program (PKH) had positive and significant effect on the welfare of very poor households in Sumbawa District. The ability of the Family Hope Program (PKH) implementation variable to effect the welfare of very poor households (RTSM) in Sumbawa District was 63.6%, while the remaining of 36.4% was influenced by other variables outside this study model, such as open unemployment, per capita expenditure, and GRDP.